The Cambridge companion to feminism in philosophy - Fricker, Miranda; Hornsby, Jennifer (United Kingdom, 2004)
The book intends to foster appreciation of the potentially far-reaching impact of feminist thinking in philosophy.
Keywords: Feminism- Philosophy